WASTE ECONOMIES: LOCAL PERSPECTIVES ON GLOBAL INEQUALITIES - Doron, Assa (International Conference on Cultural Studies, 2018)
In this seminar I look at some key cultural and social concerns fuelling the crisis of waste in the world, with specific focus in India. I propose a series of consideration regarding the potential nexus of environmental pollution, social and cultural prejudice and global power relations. Such consideration illustrate how each problem waste, inequality and environmental pollution – will fundamentally shape one – another over the purse of the coming decades, with differential impacts across socio – economics divides.